Diagnosis and Management of Hyperkalemia - Tinawi, Mohammad (Archives of Clinical and Biomedical Research, 2020)
Potassium (K+) is the most abundant intracellular cation. Intracellular K+ concentration is around 150 mEq/l, while its extracellular concentration is 3.5-5 mEq/l. Serum K+ is determined by intake, excretion, and transcellular distribution. The kidneys and the adrenal glands regulate K+ excretion. Hyperkalemia is mainly seen in patient with impaired renal function (acute kidney injury or advanced chronic kidney disease) or in patients with decreased mineralocorticoid (aldosterone) activity. Certain medications can result in hyperkalemia in patients with impaired renal K+ excretion. Aldosterone is the key regulator of renal K+ excretion. Hyperkalemia (serum K+ ≥ 5.5 mEq/l) has multiple manifestations; however, cardiac arrhythmias are the most serious. Detailed history and basic laboratory tests are required to diagnose hyperkalemia. Hyperkalemia is treated medically; hemodialysis is reserved for severe and emergency cases.